Factors Affecting the Digestibility of Beef and Consequences for Designing Meat-Centric Meals - Mustafa M. Farouk; Guojie Wu; Deborah A. Frost; Maryann Staincliffe; Scott O. Knowles (Journal of Food Quality)
The impact of the following on beef digestibility was determined by static in vitro methods: (1) age of cattle; (2) muscle rigor state, ultimate pH, and mincing/particle size; (3) muscle/meat cut; (4) organ meats; and (5) meat accompaniments. Results indicate that beef is more digestible from older compared to younger cattle; prerigor compared to postrigor meat; higher compared to lower ultimate pH meat; cuts with lower compared to higher collagen contents; finely compared to coarsely minced/ground meat; and organ (liver and kidney) compared to muscle meat. Beef digestibility is enhanced when cooked with mushroom and pumpkin and reduced with starchy foods such as rice and potatoes. The outcomes of this study provide a base for the scientific design of meals with beef as a central ingredient and digestibility as the main functionality of interest.